Prinsip-Prinsip Rohani Mengenai Pengembangan Potensi Diri Suatu Tinjauan Praktis dalam Matius 25: 14-30 - Amelia (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2022)
This research intends to analyze how to develop and maximize the potential of the self that God has given with the aim of God's glory. This research method uses a literature study. Based on the author's study in the Bible, especially in the Gospel of Matthew 25: 14-30, the author finds several spiritual principles that must be understood regarding the development of self-potential so that a person can develop their potential properly and responsibly. In this text, Jesus is explaining the Kingdom of Heaven through a parable of a person who wants to travel and entrusts his property to entrusted people. It is clear that Jesus is emphasizing some important spiritual principles regarding how one should develop the potential and opportunities that one has been given. Without having the right understanding and awareness of the need to develop one's potential based on the truth of God's Word, one will never maximally develop one's potential in life as desired by God.